Continuous, edge localized ion heating during non-solenoidal plasma startup and sustainment in a low aspect ratio tokamak. (16th May 2017) - Burke, M.G.; Barr, J.L.; Bongard, M.W.; Fonck, R.J.; Hinson, E.T.; Perry, J.M.; Reusch, J.A.; Schlossberg, D.J.
Abstract: Plasmas in the Pegasus spherical tokamak are initiated and grown by the non-solenoidal local helicity injection (LHI) current drive technique. The LHI system consists of three adjacent electron current sources that inject multiple helical current filaments that can reconnect with each other. Anomalously high impurity ion temperatures are observed during LHI with T i, OV   ⩽  650 eV, which is in contrast to T i, OV   ⩽  70 eV from Ohmic heating alone. Spatial profiles of T i, OV indicate an edge localized heating source, with T i, OV ~ 650 eV near the outboard major radius of the injectors and dropping to ~150 eV near the plasma magnetic axis. Experiments without a background tokamak plasma indicate the ion heating results from magnetic reconnection between adjacent injected current filaments. In these experiments, the HeII T i perpendicular to the magnetic field is found to scale with the reconnecting field strength, local density, and guide field, while T i, ∥ experiences little change, in agreement with two-fluid reconnection theory. This ion heating is not expected to significantly impact the LHI plasma performance in Pegasus, as it does not contribute significantly to the electron heating. However, estimates of the power transfer to the bulk ion are quite large, and thus LHI current drive provides an auxiliary ion heating mechanism to the tokamak plasma.